The Influence of Brand Image and Brand Ambassador on Intention to Purchase Scarlett Whitening Products - Sesilia Vani Susanto; Aida Sari; Dwi Asri Siti Ambarwati (Asian Journal of Applied Business and Management, 2023)
Beauty trends are currently starting to penetrate the global market, including Indonesia. One of them is Scarlett Whitening, a local beauty brand that sells skin care and beauty products made from natural ingredients. Scarlett Whitening launched its official product on the Indonesian market in 2017. This research discusses the influence of brand image and brand ambassadors on purchase intentions for Scarlett Whitening products in Bandar Lampung. Research participants were consumer users and those who knew the product and brand ambassador Scarlett Whitening, totaling 100 respondents. The research was conducted using quantitative methods with data collection methods using Purposive Sampling Techniques. The analysis techniques used in this research are multiple linear regression test and partial hypothesis testing (T test). The results of this study show that brand image and brand ambassadors have a positive and significant effect on purchase intention Scarlett Whitening products